math

posted by .

solve using substitution

3x-4y=-5
x=y+2
HELP Me.!

• math -

This one is easy. x is already expressed in terms of y in the second equation. You only have to replace the x in the forst equation with the expression from the second equation. You get that:

3*(y+2)-4y=-5
=>3y+6-4y=-5
=>6-y=-5
=>y=11

When we place this value for y in the second equation, we find that

x=11+2=13

So, y=11 and x=13

Similar Questions

1. Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. Math

how do you solve this system? I'm using substitution.. y=3x+4 y=-x^2 First I combined it: -x^2=3x+4 I don't know how to solve it now..
3. math

solve each system of equations by substitution. y=3x-9 please help explain how to solve this using substitution.
4. algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
5. Calculus 2

Evalute the integral of x/(x^2+4)dx using u-substitution and then trigonometric substitution. I did this and got (1/2)ln(x^2+4)+C using u-substitution and x^2+4+C using trigonometric substitution. What did I do wrong?
6. math/ elimination& substitution

how do i solve this? using elimination or substitution?
7. Math

Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using elimination y - 1/2x = 6 2x + 6y = 19
8. Math help

Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using elimination y - 1/2x = 6 2x + 6y = 19